Releitura do contos de fadas por meio de cordéis na perspectiva do letramento literário - Pereira, Ângela Márcia Fernandes (2020)
The teaching of literacy in schools has been relegated to the background and for this reason it has always been the target of questioning by theorists and specialists in the area and, also, due to the failure of the applied methodologies that aim at the literary literacy of the student. In order to change this reality and promote more meaningful reading practices of literary texts, we thought of teaching strategies that would awaken the student's reading awareness and that, equally, promote the construction of a subject who knows how to interact, build, reconstruct and resignify himself universe itself through the word. Following this direction, we carried out work with 6th grade students of Elementary School II, from a public school in the Federal District. We believe that the intertextual work between cordel leaflets and fairytales would be significant for the formation of the student’s literary and linguistic competence and, in the same way, for the development of his critical sense. The representation of women was the theme that intertwined cordel and fairytale narratives intertextually. Thus, based on the Basic Sequence of literary literacy suggested by Rildo Cosson (2014), we proposed workshops that instigated literary reading and writing in students and that, likewise, encourage reflection on the place that women occupy in literature. The research proposal consisted of conducting a bibliographic study on literary literacy, schooling of literature and intertextuality in the teaching of literary genres based on a specific theoretical apparatus. In addition, it was also our goal to promote intertextuality between the cordel genre and the fairy tale genre, through workshops aimed at reading and writing leaflets that addressed the issue of women, enabling a review of the female image consistent with reality current, which is about fighting for gender equality and seeking to expand spaces for female occupation